Privatization for economics prosperity or poverty - A case of Pakistan - Amer, Shaukat (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
Privatization is a complex exercise with multifaceted implications and has to be conducted with a number of caveats (Khan, 2001).The present privatization process of State Owned Enterprises (SOEs) started in Pakistan in 1991 under pressure form donor agencies without formulating a rational privatization policy. This includes establishing a proper business environment, regulatory regime and development of financial markets to create potential for the purpose. The privatization process was criticized during all the governments. The capital markets in Pakistan are not so developed. So, as was done in some cases, it is better that all the wholly owned units by the government are first converted into public limited companies and than the shares are offered to a wide range of investors specially targeting overseas Pakistanis and Arab world. It is never too late, still units having real worth of billion of dollars are there to be privatized. A major shift in the privatization policy can not only facilitate the government of Pakistan to eliminate completely the foreign debt but also this will align and enhance economic activities in the shape of effective and efficient management both in public and private sectors business units. In view of bail out packages by the state, its role to own business units has been reemerged. And if at all privatization is still desirable it should be in a different mode according to the changed scenario with the ultimate aim of economic prosperity.